KAJIAN FREKUENSI PENYIANGAN DAN PEMBERIAN PUPUK N TERHADAP PERTUMBUHAN GULMA DAN HASIL PADI (Oryza sativa L.) VARIETAS MUGIBAT DALAM SISTEM SALIBU - Indri Priani; Darnawi Darnawi; Maria Theresia Darini (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the frequency of weeding and N fertilizer application to weed growth and rice yield (Oryza sativa L.) varieties involved in the salibu system. The research was conducted at the Self-Supporting Agriculture and Rural Training Center P4S Lestari Makmur, Jl. Wates Km.12 Pollaman of Argorejo Village, Sedayu District, Bantul Regency, Special Region of Yogyakarta. The research location at altitude is Â± 149 meters above sea level, temperature 24.5 - 32.5 â„ƒ, with rainfall 1500 - 2000 mm per year, air humidity 65 -95%. The study was conducted in March - June 2018. The study used experimental methods Randomized Completly Block Design (RCBD) with factorial 2x3. The first factor was the weeding frequency (P) at one time (P1) and twice (P2). The second factor was the frequency of fertilization (N) which consists of three levels, namely the one-time fertilization frequency (N1), twice the fertilization frequency (N2), and three times the fertilization frequency (N3). Total combination of 2x3 = 6 combinations. Each treatment consisted of three replications of five plant samples. Observation variables included number of tillers, plant height, weed types, weed fresh weights, weed dry weight, and harvested dry grain weight per hectare. Analysis of results with variance at 5% real level, followed by Duncan Multiple Range Test (DMRT) and level of 5%. the results of this study showed no interaction between the frequency of weeding and N fertilizer application, but the frequency of weeding showed a significant difference in the number of tillers and weed types, whereas the application of N fertilizer showed significant differences in weeds fresh weight variables, weed dry weight, and yield of harvested dry grain per hectare